Dining hall management system - Chikondowa, Tinevimbo (Midlands State University, 2018)
The purpose of the study was to develop and implement an information system that serves the needs of Chinhoyi University of Technology Dining hall personnel, management and students. For management the system helps in the analysis and provision of information that supports management functions The research exposed the value and the ability of the organization to undertake the project considering the timeframes and other material resources. With close scrutiny of the findings on how the system operates the developer decided to undertake the project in order to improve efficiency through the use of C#, crystal reports and mysql database server. In the quest to develop a system that is acceptable to the organization, the developer used various information gathering techniques that include questionnaires, interviews and observation in a bid to elicit the challenges the stakeholders had with the manual system. The formulation of basic system functionality of the product to be developed were done through the use of data flow diagrams, entity relationship diagrams for the sake of bringing the conceptual being of the system. Moreover menu; interface; input; and output models were constructed. The logical structures were further turned into specific tested instructions that are to be executed by the computer system. With the following considerations a changeover method was selected which included; risk control, pace of change, and need for facilitation of change. The developer recommends that the users stick to the basics learnt during the training period for any challenges they should refer to the comprehensive user manual. Security measures were considered through use of user names and passwords thus restricting access to certain privileges to some users. To cater for changes in user requirements system maintenance will be provided when the need arise.